The evaluation of toxicological data for the protection of public health : proceedings of the International Colloquium, Luxembourg, December 1976 - Hunter, W. J. (William John), 1937-; Smeets, J. (EUR, 1977)
The Evaluation of Toxicological Data for the Protection of Public Health: Proceedings of the International Colloquium, Luxembourg, December 1976 focuses on the review of toxicological tests and methods used in toxicological evaluation of chemicals and reconsideration of these procedures in identifying decision-making processes involved in the protection of public health. The selection first discusses reviews of toxicological tests, including introductory remarks and comments on acute toxicity; problems associated with the testing of environmental mutagens; and the testing of carcinogenic poten.